Analysis of risk factor microflora colonization on pregnancy vagina in Makassar - Fardi; Rezeki Nur; Dewi Hestiani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: Worldwide infection rates based on estimated 20-30 % colonization at 35 weeks gestation. During normal pregnancy, colonization is transient, intermittent, or chronic infection, and the spectrum varies from asymptomatic colonization to sepsis. Intrapartum transmission of bacteria from mother to neonatal will cause the infection to develop into neonatal sepsis during childbirth. This study aimed to determine the proportion of gram-positive and negative bacteria colonization in pregnant women over 31 weeks of age. Research Methodology: This research uses vaginal swab samples from pregnant women and blood samples from babies who are born, then these samples will be examined in the Unhas Hospital laboratory. Vaginal swab samples via transport medium will be placed in BHIB medium and then incubated at 270 C for 24 hours. Result: Prevalence of gram-positive bacterium identified Streptococcus species (0.9%), S. Aureus (11.8%), and S. Epidermidis (78.4%). For gram-negative bacteria identified, Enterobacter Sp (32.3%), Providencia Sp (12.7%), Proteus Sp (8.8%), Acinetobacter sp (5.9%), and E. Coli (6.9%). Candida Sp was obtained on SDA culture and gram staining, followed by several 54 samples (55.1%). The symptom was to be Discharge Vagina in over 30% of cases. Of 76.6% were habitually antiseptic. Based on data and statistical analysis, it can be concluded that age has a significance level of 0:01 (ρ < 0.05), and contraceptives used to have a significance level of 0.038 (ρ < 0.05), had a relationship with a potential fetomaternal infection to the infant. Conclusion: Maternal age and history of contraceptive use are significantly associated with bacterial colonization in pregnant women. These findings underscore the need to consider demographic and behavioral factors when assessing and managing vaginal health during pregnancy. Effective educational interventions focusing on proper hygiene practices and the risks associated with antiseptic soap use, coupled with targeted monitoring of older pregnant women and those with a history of contraceptive use, are recommended to reduce the risks associated with vaginal microbial colonization.